Application of ontological information system for the selection of anaerobic digestion equipment - Tarasenko, Roman; Usenko, Stanislav; Shapovalov, Yevhenii; Shapovalov, Viktor (My University, 2020)
Ontology widely used to support various types of information management including information retrieval, storage, and sharing on the web. To construct ontologies special software are using, which allows users to build hierarchies and create semantic links. A range of open-source and commercial tools are available. They assist in the development of various ontologies, and called Ontology Editors.
Keywords: кафедра харчової хімії; IT-platform polyhedron; ontology; anaerobic digestion equipment; selection of equipment; онтологія; підбір обладнання; IT-платформа Багатогранник; обладнання для анаеробної ферментації